Penerapan Role Play Dengan Aplikasi Kasir Pintar Untuk Meningkatkan Kemampuan Pengelompokan Nilai Bilangan - Tanjung, Febryna Alawiyah; Robandi, Babang (Peneliti.net, 2025)
This research aims to improve the ability of grade 5 students at SDN 077 Sejahtera Bandung in grouping place values ​​of numbers through the use of the Smart Cashier application. Based on initial observations, many students have difficulty understanding the concept of place value of numbers, which is reflected in the low evaluation results on this material. This classroom action research (PTK) uses a learning method based on buying and selling transaction simulations with the Smart Cashier application and involves making play money as a visual aid. The research was carried out in two cycles, where each cycle consisted of planning, implementation, observation and reflection stages. The research results showed that the application of this method succeeded in significantly increasing students’ understanding of the concept of place value of numbers. Students not only find it easier to understand the concept, but also show high enthusiasm during the learning process. This increase is also reflected in the evaluation results which show an increase in students’ mathematics scores in place value material. The average student score experienced a significant increase, where more than 85% of students succeeded in achieving the Minimum Completeness Criteria (KKM) after implementing this method. In conclusion, the use of the Smart Cashier application as an interactive learning medium has proven to be effective in improving students’ ability to group place values ​​of numbers, as well as encouraging active participation and enthusiasm for students in learning mathematics. The results of this research can be a reference for teachers to implement internal technology learning to improve the quality of student learning outcomes.